Computational investigations of mesenchymal stem cell ageing in mechanobiological simulations of tissue differentiation - Xue, Feng (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2014)
Musculoskeletal health is a major determinant of the quality of life for the increasing aged population groups in our society. Improved healthcare is essential to ensure successful ageing and enhanced musculoskeletal health is pivotal for tackling age-associated diseases such as osteoporosis and osteoarthritis. The primary clinical solutions for treating such diseases are well established for the young population. However, for these therapies to be successful in elder age groups, for whom tissue repair is mostly needed, it is important to understand the influence of mesenchymal stem cell (MSC) ageing to the tissue differentiation.
Keywords: Bioengineering, Ph.D.; Ph.D. Trinity College Dublin